2018
DOI: 10.1155/2018/1893195
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Soil Grouting with Cement Slurry and Cement‐Sodium Silicate Slurry

Abstract: Cement slurry and cement-sodium silicate slurry are most widely applied for soil grouting reinforcement project. e viscosity change of cement slurry is negligible during grouting period and presumed to be time independent, while the viscosity of cementsodium silicate slurry increases with time quickly and is presumed to be time dependent. Due to the significant rheological differences between them, the grouting quality and the increasing characteristics of grouting parameters may be different. ose are main fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It has been applied across all ranges of weak soils such as clay soil, black cotton soils, and organic soils among others. Cement has been utilized mostly as a binder and it has been proven to improve the engineering properties of soils (Prusinski & Bhattacharja, 1998) (Binh & Quynh, 2021;Zhu, Zhang, Zhang, & Hui, 2018). With the cost of cement being quite high and other stabilizing materials being discovered, cement has been used in presence of other materials to lower the amount of cement required and help improve on other geotechnical properties that cement alone cannot effectively improve.…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied across all ranges of weak soils such as clay soil, black cotton soils, and organic soils among others. Cement has been utilized mostly as a binder and it has been proven to improve the engineering properties of soils (Prusinski & Bhattacharja, 1998) (Binh & Quynh, 2021;Zhu, Zhang, Zhang, & Hui, 2018). With the cost of cement being quite high and other stabilizing materials being discovered, cement has been used in presence of other materials to lower the amount of cement required and help improve on other geotechnical properties that cement alone cannot effectively improve.…”
Section: Introductionmentioning
confidence: 99%
“…The interior of the rock was developed generally with a large number of different sizes and forms of fractures, and it was of great importance to select an appropriate grout material to control the performance of different fractured rocks [4]. For the rock with deep fractures and micropores, chemical grout with low viscosity and adjustable gel time such as paste grout, silica solutions, hot asphalt grout, and polyurethane grout [5][6][7] was needed to increase the fluidity and ensure the compactness after grouting [8,9]. The fluidity of fluids was not only related to the type of material but also varied with the pressure and temperature of the fluids [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…According to the viscosity characteristics of slurry, Zhu et al [ 20 ] found that the viscosity of cement slurry changed little in the process of grouting, while the viscosity of cement-sodium silicate slurry increased rapidly with the increase of time. Yang et al [ 21 ] and Du et al [ 22 ] have done a lot of research on the variation law of the viscosity of all kinds of slurry, and proved that the viscosity of the slurry has time-varying characteristics, but the specific law of the time-varying viscosity of the slurry has not been deeply studied.…”
Section: Introductionmentioning
confidence: 99%